Quantum confinement-induced tunable exciton states in graphene oxide - Lee, Jaichan (2013)
Graphene oxide has recently been considered to be a potential replacement for cadmium-based quantum dots due to its expected high fluorescence. Although previously reported, the origin of the luminescence in graphene oxide is still controversial. Here, we report the presence of core/valence excitons in graphene-based materials, a basic ingredient for optical devices, induced by quantum confinement. Electron confinement in the unreacted graphitic regions of graphene oxide was probed by high resolution X-ray absorption near edge structure spectroscopy and first-principles calculations. Using experiments and simulations, we were able to tune the core/valence exciton energy by manipulating the size of graphitic regions through the degree of oxidation. The binding energy of an exciton in highly oxidized graphene oxide is similar to that in organic electroluminescent materials. These results open the possibility of graphene oxide-based optoelectronic device technology.